Glycocalyx Impairment in Vascular Disease: Focus on Inflammation - Qu, Jing; Cheng, Yue; Wu, Wenchao; Yuan, Lixing; Liu, Xiaojing (Frontiers in Cell and Developmental Biology, 2021)
Glycocalyx is a polysaccharide-protein complex layer on the side of vascular endothelial cell lumen. Many studies have confirmed that changes in the structure and function of glycocalyx promote inflammatory response in blood vessels under inflammatory conditions, and play an important role in the pathogenesis of many vascular diseases (in particular, derived from diabetes, atherosclerosis and sepsis). Vascular endothelial dysfunction is one of the hallmarks of inflammation-related diseases. Endothelial dysfunction may lead to tissue swelling, chronic inflammation and thrombosis. Therefore, the elimination of endothelial inflammation could be a potential target for the treatment of vascular diseases. This review summarizes the key role and possible mechanism of glycocalyx alleviating this process by interrupting the vicious circle between endothelial dysfunction and inflammation. Especially, we highlight the impact of different components of glycocalyx in regulating the inflammatory process, including regulating leukocyte rolling as ligands of L-selectin, regulating the inflammasome activation and so on. Taken together, we expound the pattern of glycocalyx interferes with inflammation development and the significance of preventing glycocalyx impairment, and provide a potential strategy for treatment of vascular diseases.